Pengaruh Motivasi dan Penilaian Prestasi Kerja terhadap Kepuasan Kerja Karyawan pada PT PA Rubber Indonesia Jaya - Jojon Soesatrijo (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
This research study purpose to determine whether there is a significant influence of motivation and work performance appraisal on employee job satisfaction at PT PA Rubber Indonesia Jaya. There are three hypotheses tested in this study. First there is a positive influence of motivation on employee job satisfaction, secondly there is a positive influence on job performance assessment on employee job satisfaction, thirdly there is a positive influence of motivation and work performance assessment together on employee job satisfaction. The population of this research were employees of the company, ie 160 people, while the sample was 114 people taken from the population randomly using simple random sampling technique. Data research instruments use three types of tools, namely questionnaires that use a likert scale. The questionnaire was prepared based on the construction of various theories. Data analysis was carried out at 95% confidence level. The result is significantly proven all the existing hypotheses. So the results of this study inform that the motivation and assessment of work performance variables are important factors in increasing employee job satisfaction at PT PA Rubber Indonesia Jaya.